Comparison of sporadic and familial behavioral variant frontotemporal dementia (FTD) in a North American cohort. Issue 1 (8th January 2020) - Heuer, Hilary W.; Wang, P.; Rascovsky, K.; Wolf, A.; Appleby, B.; Bove, J.; Bordelon, Y.; Brannelly, P.; Brushaber, D.E.; Caso, C.; Coppola, G.; Dickerson, B.; et al.
Abstract: Introduction: Behavioral variant frontotemporal dementia (bvFTD) may present sporadically or due to an autosomal dominant mutation. Characterization of both forms will improve understanding of the generalizability of assessments and treatments. Methods: A total of 135 sporadic (s‐bvFTD; mean age 63.3 years; 34% female) and 99 familial (f‐bvFTD; mean age 59.9; 48% female) bvFTD participants were identified. f‐bvFTD cases included 43 with known or presumed chromosome 9 open reading frame 72 ( C9orf72 ) gene expansions, 28 with known or presumed microtubule‐associated protein tau (MAPT) mutations, 14 with known progranulin ( GRN ) mutations, and 14 with a strong family history of FTD but no identified mutation. Results: Participants with f‐bvFTD were younger and had earlier age at onset. s‐bvFTD had higher total Neuropsychiatric Inventory Questionnaire (NPI‐Q) scores due to more frequent endorsement of depression and irritability. Discussion: f‐bvFTD and s‐bvFTD cases are clinically similar, suggesting the generalizability of novel biomarkers, therapies, and clinical tools developed in either form to the other.